Mapping flood-prone areas in Bangladesh and assess how climate change will impact future flood risks - Rahman,Prangshu Md Naziur (Student thesis series INES, 2025)
Bangladesh faces recurrent and severe flooding due to its low-lying topography and intense monsoon climate, making it one of the most flood-prone countries in the world. These floods pose significant threats to human life, infrastructure, and economic stability which is projected to intensify under future climate change scenarios. This thesis presents a flood susceptibility assessment using the Analytic Hierarchy Process (AHP) combined with Geographic Information Systems (GIS). Eight key environmental and hydrological factors were considered for this spatial overlay analysis. Flood susceptibility maps were generated for three time periods — current, near future (2024–2060), and far future (2061–2100), using precipitation projections from the CMIP6 model, Beijing Climate Centre Climate System Model (BCC-CSM2-MR) under the SSP2-4.5 scenario. The results show a clear increase in high and very high flood susceptibility zones, expanding from 57% of the country currently to 66% by 2060 and remains relatively similar to the end of 2100, with the most affected areas in central and northeastern Bangladesh. The model's predictive accuracy was confirmed through Receiver Operating Characteristic (ROC) curve, with an Area Under the Curve (AUC) value of 0.79, indicating good reliability. These findings emphasize the urgent need for adaptive strategies in flood management and land-use planning. The study offers a spatially framework to support evidence-based decision-making for reducing flood risk in Bangladesh in the face of climate change.
Keywords: Flood susceptibility mapping in Bangladesh using GIS; AHP; CMIP6 precipitation; and multivariate analysis